BMS-871: A novel orally active pan-Notch inhibitor as an anticancer agent. Issue 9 (1st May 2015) - Shan, Weifang; Balog, Aaron; Quesnelle, Claude; Gill, Patrice; Han, Wen-Ching; Norris, Derek; Mandal, Sunilkumar; Thiruvenkadam, Raja; Gona, Kiran Babu; Thiyagarajan, Kamalraj; Kandula, Sathiah; McGlinchey, Kelly; et al.
Graphical abstract: Abstract: This Letter describes synthesis, SAR, and biological activity of (2-oxo-1, 4-benzodiazepin-3-yl)-succinamides as inhibitors of γ-secretase mediated signaling of Notch receptors. Optimization of this series led to the identification of BMS-871 (compound30 ) which displayed robust in vivo efficacy in Notch-dependent leukemia and solid tumor xenograft models.